The present state of knowledge of the insect fauna o f the Bolimów Landscape Park, with particular reference to the river Rawka’s valley - Kowalczyk, Jan; Krzeptowski, Maciej; Lenkowski, Tomasz; Majecki, Janusz; Marciniak, Barbara; Mastalerz, Maciej; Myślicka, Zdzisława; Nadolski, Jerzy; Wanat, Marek (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
During the study, 653 species of insects have been found in the Bolimów Landscape Park, including 62 rare and interesting species. Among them the beetle Aderus peniaiomus is a new species for the Polish fauna. Many species occurring here are new for the Mazovia region.